Rekonstrukcija međukolodvora na pruzi Vinkovci-Novska za prolazne brzine 160 km/h - Levar, Zdenko (Promet - Traffic&Transportation)
The author deals in this paper with a review of reconstruction of intermediate stations for accommodation to transit speeds of 160 km/hr on the double track section of the Beograd-Zagreb rail on the Vinkovci-Novska route section with reference to the overall issue regarding the introduction of the speeds of 160 km/hr.